2004
DOI: 10.1259/dmfr/13603271
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial measurements based on 3D-CT volume rendering: implications for clinical applications

Abstract: 3D-CT volume rendering images using craniometric measurements can be used for anthropological studies involving craniofacial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
27

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(138 citation statements)
references
References 21 publications
6
105
0
27
Order By: Relevance
“…Our findings indicated that the mean differences between the 3D computer-assisted cephalometric and manual cephalometric measurements were less than 2 mm for all 29 measurements, and they showed the accuracy of 3D computer-assisted cephalometry, which is in line with the results of Cavalcanti et al, 10 Lopes et al, 30 and Bassam et al 31 The authors suggested performing cephalometric analysis on 3D-rendered models, which seemed to be the most appropriate approach in terms of accuracy and convenience. The comparison of manual and conventional cephalometric measurements indicated significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicated that the mean differences between the 3D computer-assisted cephalometric and manual cephalometric measurements were less than 2 mm for all 29 measurements, and they showed the accuracy of 3D computer-assisted cephalometry, which is in line with the results of Cavalcanti et al, 10 Lopes et al, 30 and Bassam et al 31 The authors suggested performing cephalometric analysis on 3D-rendered models, which seemed to be the most appropriate approach in terms of accuracy and convenience. The comparison of manual and conventional cephalometric measurements indicated significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…7,8 The accuracy of 3D-rendered images had been previously evaluated, 9,10 and the findings showed that direct 3D measurements were highly accurate, with no significant discrepancies from manual measurements. 3D imaging techniques comprise a noninvasive method.…”
Section: Introductionmentioning
confidence: 99%
“…However, patients usually evaluate their own soft tissue esthetics on the basis of how they look in a frontal view. Therefore, three-dimensional (3D) imaging methods, such as 3D computed tomography [3][4][5][6] and 3D facial scan images (3D-FSIs), [7][8][9][10][11][12] are used to analyze and evaluate the soft tissues of the entire face.…”
Section: Introductionmentioning
confidence: 99%
“…TC Cone-Beam 3D -Os parâmetros utilizados para a análise das VAS foram obtidos com a análise volumétrica das vias aéreas [29], com a utilização da tomografia computadorizada de feixe cônico (TCCB). As imagens foram adquiridas com um tomógrafo de feixe cônico I-CAT (I-CAT ™ Imaging Sciences International, Hatfield, PA) que se utiliza de um tubo de raios-X de alta frequência de anodo fixo (120 kVp, 3 ~ 8 mA) e um detector de tela plana de silício amorfo (a-Si) de 20 x 25 cm.…”
Section: Materiais E Métodosunclassified